Writing English Essays Within Dominant Discourses In Malaysian Schools - Tan , Kok Eng (Penerbit Universiti Sains Malaysia, 2006)
Writing is one of the four English language skills taught and tested in the education system in Malaysia. At the upper secondary school level, students write a variety of text types, most of which conform to examination genres. Given a learning context that is examination-driven and teacher-centred, and a writing curriculum that is non-negotiable, how do students accomplish their writing tasks? Embedding the classroom in an institutional and a larger sociocultural context, this paper demonstrates how some students responded to teacher instructions such as "Read, understand, interpret, do" and "Strictly no discussion please." Data were taken from student interviews, teacher interviews, students' written products and classroom observations of writing lessons over the second half of the school year. Findings from the study show the students' compliance with their teacher's expectations and writing requirements for school and examination purposes. It was a strategy to "get it done" but within school sanctions. In out-of-school contexts, students were engaged in other contrasting types of writing in English which served other social purposes.